Dynamic of Death Anxiety in People with Gastroesophageal Reflux Disease - Mohammad Zarkasi; Ahmad Saifuddin (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Gastroesophageal reflux disease (GERD) is a disease that many individuals suffer from. Some GERD patients even develop death anxiety due to their health condition. This qualitative study aimed to explain the dynamic of death anxiety in people with GERD and used a phenomenological approach. The informants were three adult men who had been diagnosed with GERD for more than six months. The stages of data analysis included horizontalization, textural description, structural description, and phenomenon description. Meanwhile, the data validity techniques used were member checking and time triangulation. The three respondents displayed death anxiety aspects proposed by previous studies. Findings revealed that GERD patients who experienced death anxiety also experienced hypochondria symptoms and future doubts. Participants further reported death anxiety was unrelated to age, life stability, and serious illness type.